Classism in pain assessment and management: the mediating role of female patient dehumanization and perceived life hardship. Issue 12 (22nd December 2021) - Bernardes, Sónia F.; Tomé-Pires, Catarina; Brandão, Tânia; Campos, Lúcia; Teixeira, Filipa; Goubert, Liesbet
Abstract : Chronic pain patients' dehumanization and perceived life hardship account for some effects of the patient socioeconomic status on medical students' and nurses' pain assessment and management practices. Abstract: Compared with racism and sexism, classism in pain assessment and management practices (PAMPs) has been less investigated, and its mediating mechanisms are still unknown. Drawing on a social psychological model of dehumanization, this research aimed to test (1) the effect of patient socioeconomic status (SES; a proxy of social class) on PAMPs and (2) whether patient dehumanization and perceived life hardship mediated these effects. Two online experimental studies were conducted, in which patient SES was manipulated (low vs high) within-subjects. One-hundred sixty-two female medical students (study 1) and 105 female nurses (study 2) were presented with vignettes/images depicting 2 cases of women with chronic low-back pain, followed by videos of them performing a pain-inducing movement. Participants reported on patient dehumanization, perceived life hardship, and PAMPs. The low SES patient was perceived as less pain sensitive (medical students alone) but more disabled, credible, and her pain more attributed to psychological causes (by nurses alone). Medical students recommended less nonpharmacological treatments but prescribed slightly stronger medication. Medical students were less willing to provide individualized care to the low SES patient, whereas nurses showed the opposite pattern. Patient mechanistic dehumanization mediated SES effects on pain disability (medical students alone). Perceived life hardship mediated SES effects on pain disability, credibility (nurses alone), and intentions of providing individualized care (nurses alone). These finding bear novel contributions to the fields of pain, health service research, and social psychology and have important implications to the development of more effective future interventions to reduce classism in PAMPs.